The Foz Tua arch dam design - Matos , D. (2011)
Abstract. Portugal is presently facing a new hydroelectricity era, with the implementation of a large development program including not only the power upgrade of existing large hydro schemes, but also the construction of several new ones, almost all of them considered in the “National Program of Dams with High Hydroelectric Potential”, dated of December 2007. EDP-Energias de Portugal was awarded the concession of three hydroelectric schemes included in this Program and Foz Tua Hydroelectric Project was the first one to be launched. The Project is located in the North region of Portugal, in the Tua River, an important tributary of Douro River, close to its confluence into Douro River. The feasibility study of this scheme was developed by EDP in 2008, which included a complete environmental assessment of the project envisaging the Authorities approval. Actually the project has been submitted for approval with the defined Environmental Conformity Report and EDP has already received the contractor’s proposals to the Project construction, which will start in 2011. The project includes a double curvature arch dam, 108 m high provided with a surface controlled spillway over its crest designed for a 5500 m3/s flood, an hydraulic circuit in the right bank, about 700 m long, composed of two independent tunnels and a downstream powerhouse equipped with two reversible units with a rated output of 131 MW each one. After a general description of the project, the paper details the structural analysis performed to the dam design and to foresee the dam-foundation behavior according to the Portuguese Regulation requirements. Furthermore, structural analysis carried out by the National Laboratory of Civil Engineering (LNEC) to assess the dam safety with respect to failure scenarios are also presented, namely involving concrete damage, foundation failure and the maximum design earthquake effects.